The Influence of Human Resource Competence on the Quality of Local Government Financial Statements with Internal Control Systems as a Mediating Variable - Asah, Antung Noor; Syahdan, Saifhul Anuar; Boedi, *, Soelistijono; Ernawati, Sri; Ruwanti, Gemi (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to examine the influence of human resource competence on the quality of financial statements, with internal control systems as a mediating variable. The research was conducted using a quantitative method. Primary data were utilized, obtained directly from respondents’ answers to the distributed questionnaires. The population in this study consists of Regional Government Work Units (Satuan Kerja Perangkat Daerah or SKPD) in Banjarbaru City. The sampling technique employed was purposive sampling, with the sample consisting of planning and finance section heads, finance staff, treasurers, and secretaries. A total of 67 respondents were selected as the research sample. The results of the study indicate that human resource competence has a positive effect on internal control and the quality of local government financial statements. Internal control systems also have a positive effect on the quality of local government financial statements, and internal control systems mediate the relationship between human resource competence and the quality of local government financial statements.